A transient current protection and fault location scheme for MMC-HVDC transmission network. (January 2021) - Zheng, Xiaodong; Nadeem, Muhammad Haroon; Tai, Nengling; Habib, Salman; Wang, Biqi; Yu, Moduo; He, Yangyang
Highlights: A transient current protection scheme is proposed in this paper. Relation between fault current and transient current variations is utilized. Transient current polarities are used to distinguish internal and external faults. The increment in the transient current localized the fault location. Two terminal MMC-HVDC model is tested in RTDS. Fault resistance and distance affecting protection scheme performance are analyzed. Abstract: The relation between fault current waves and variations of transient current in dc transmission lines (DC-TL) is meticulously investigated under numerous fault conditions. On these grounds, a transient current protection scheme is proposed for modular multi-level converter high voltage dc (MMC-HVDC). By using the wave propagation theory, the transient current distribution over the line can be acquired from current at both ends of DC-TL and fault can be localized from the approximate calculated results. Additionally, the sited fault can be precisely computed in case of internal faults. Two terminal MMC-HVDC model is tested in real-time digital simulator (RTDS) for analyzing the application of the proposed scheme. Comprehensive test results authenticate the promising performance of the proposed scheme. Efficient identification of internal as well as external faults with high accuracy, along with viable adoption for high ground resistance faults, is also a distinguishing feature of this scheme. Moreover, two main parameters; fault resistance and distance of fault that affect the protection scheme performance are also addressed critically.